2018
DOI: 10.3928/1081597x-20180228-03
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Comparison of Visual Outcomes After KAMRA Corneal Inlay Implantation With Simultaneous PRK or LASIK

Abstract: Simultaneous PRK/inlay and LASIK/inlay meet the U.S. Food and Drug Administration standards for efficacy and safety based on 6-month preliminary results and have similar outcomes to emmetropic eyes. [J Refract Surg. 2018;34(5):310-315.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Other surgical approaches for presbyopic compensation have been studied. Several studies reported satisfactory efficacy and safety results for corneal inlays for the treatment of presbyopia in emmetropic or previously LASIK-treated patients [29][30][31][32][33][34][35][36][37][38][39][40] . There are still concerns about the risks of infection, stromal fibrosis or melting after implantation 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Other surgical approaches for presbyopic compensation have been studied. Several studies reported satisfactory efficacy and safety results for corneal inlays for the treatment of presbyopia in emmetropic or previously LASIK-treated patients [29][30][31][32][33][34][35][36][37][38][39][40] . There are still concerns about the risks of infection, stromal fibrosis or melting after implantation 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies found the Kamra corneal inlay as safe and effective in treating presbyopia with the significant increase in the uncorrected near visual acuity (UNVA) and minimal difference in uncorrected distance visual acuity (UDVA) [ Table 3 ]. [ 1 2 3 4 11 16 17 18 19 20 21 22 23 24 ] Uncorrected intermediate visual acuity (UIVA) also improved. [ 1 17 18 24 ] The United States Food and Drug Administration (USFDA) clinical trial reported that at 3 years postoperatively, UNVA mean increase was three or more lines, mean UDVA decreased by around half a line, mean corrected distance visual acuity (CDVA) decreased by one letter at most, and visual acuities of the implanted eyes improved binocularly for all distances.…”
Section: Efficacy and Refractive Stabilitymentioning
confidence: 99%
“…[ 1 ] Simultaneous LASIK with the current Kamra inlay model showed preoperative mean UNVA of J6 (range J2 to J16) in the inlay eyes and at 5 years postoperatively was maintained at J1 or better (range better than J1 to J2) with sustained mean UDVA of 20/30. [ 23 ]…”
Section: Efficacy and Refractive Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In the calculations the ideal eye's pre-surgical refractive state for the PDCI resulted +1.75D while for the RI was emmetropia. This is equivalent to assuming that the inlay surgery was performed simultaneously with LASIK or PRK in patients who are not already at an optimal preoperative refraction, which is a common and safe clinical procedure with commercial corneal inlays [34].…”
Section: Lens Design and Characteristicsmentioning
confidence: 99%